A cryo-shocked M2 macrophages based treatment strategy promoting repair of spinal cord injury via immunomodulation and axonal regeneration effects - Ermei Lu; Kecheng Zhou; Jiansen Miao; Yanlin Zhu; Jiyao Tang; Siting Du; Yanzhen Feng; Linyuan Jiang; Tianyao Jiang; Ting Huang; Ping Li; Xinjun Miao; et al. (Journal of Nanobiotechnology)
Abstract Recovery from spinal cord injury (SCI) is often impeded by neuroinflammation, scar formation, and limited axonal regeneration. To tackle these issues, we developed an innovative biomimetic drug delivery system using liquid nitrogen-treated M2 macrophages (LNT M2) which internalized paclitaxel (PTX) nanoparticles beforehand. These were incorporated into a gelatin methacryloyl (GelMA) scaffold, creating a multifunctional, injectable treatment for single-dose administration. The LNT M2 inherited the inflammatory factor/chemokine receptors from the living M2 macrophages and thus possessing significant inflammatory neutralizing effect. In addition, the scaffold provides slow, sustained release of PTX, promoting axonal regeneration and suppressing scar formation in SCI rats. The LNT M2-based dual-functional scaffold significantly enhances motor function, reduces neuroinflammation, and accelerates axonal regeneration by modulating the inflammatory microenvironment and preventing the formation of glial and fibrotic scars. This approach combines the regenerative effects of low-dose PTX with the immunoregulatory properties of LNT M2, leading to remarkable neurological recovery in SCI rats. Moreover, the scaffold’s straightforward preparation, ease of standardization, and “ready-to-use” nature make it a promising candidate for acute SCI intervention and future clinical applications. Graphical Abstract